Anthropometrical and physiological determinants of performance in French West Indian monofin swimmers: A first approach - Hue, O.; Galy, O.; Blonc, S.; Hertogh, C. (International Journal of Sports Medicine, 2006)
To characterise the anthropometrical and physiological parameters of French West Indian monofin swimmers, seven French West Indian male competitors underwent anthropometrical measurements and physiological testing. The results were analysed in relation with their performances during national and international events (from 50- to 1500-m). We found that both anthropometrical and physiological (aerobic and anaerobic components) factors contributed to the performances of these swimmers. The results demonstrated that certain parameters consistently contributed to the global performance: aerobic parameters (maximal oxygen uptake and the second ventilatory threshold, R2 = 0.72 and 0.69, respectively), anaerobic parameters (power obtained with the counter-movement jump [R2 = 0.58] and the force-velocity test [R2 = 0.54]), leg volume (V1, R2 = 0.54) and perimeter (P1, R2 = 0.64), and fat and lean body mass (R2 = 0.76 and 0.62, respectively). Further studies are needed to compare these determinants of performance in French West Indian and European swimmers and to investigate how they contribute to swimming technique.